Dashboards Usage for Business Intelligence: Selected Case Studies (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Dashboards usage has been a quite popular topic in recent years. In modern economy every second is important in decision making process and dashboards are surely one of the main tools to help achieve that goal. For decision makers they are a very convenient way of getting aggregated information in time. Most dashboards summarize data on predefined criteria but they often provide a drill-down or comparative analysis. Almost all dashboards provide graphical representation of their data for even faster response to situation on the market. Primary goal of this paper is to show the positive effects of using dashboards in business environment. Secondary objective is to show various cases of creating and using dashboards in practice. Every dashboard is unique and usable only to people who need it. This paper will describe the basic dashboard theory and provide two case studies of dashboards implemented in two very competitive industries, telecommunications and banking. Basic dashboard creation explains how to create a dashboard in MS Excel, which can be used at a small company or the company that can’t invest in expensive technologies, and case studies analyse implementation of two dashboards implemented for day-to-day reporting and highlighting critical information to management.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.